Teaching-service articulation: challenges and potentials in the context of a multiprofessional health residence program (Research, Society and Development, 2022)
In the Unified Health System (SUS), the possibilities of teaching at the postgraduate level, in the assistance spaces, became possible through the institution of the Multiprofessional Residency in the Professional Health Area (RMPS), with the objective of training professionals to work in the SUS from the teaching-service integration. For this training process to take place effectively, there must be a well-established teaching-service articulation that meets the principles and guidelines of the SUS. Considering the relevance of a well-established teaching-service articulation, this study sought to investigate how the process of articulation between University and assistance has taken place in a RMPS Program of a Public University in the Northeast. This is a descriptive study with a qualitative approach. Managers of the Health Units where RMPS residents are allocated, preceptors, tutors and program coordinators participated in this study. Participants collaborated with the study by completing a Sample Characterization Questionnaire (QCA) and conducting an individual interview in a virtual way, through the Google Meet application. The results were examined using Bardin's content analysis. 17 professionals participated in this study. From the analysis of the interviews, four thematic categories and eight subcategories emerged. Based on the results, professionals understand the concept and application of teaching-service integration, as well as their contributions to health services and training of residents. The interviewees pointed out weaknesses and deficiencies that have influenced the development of RMPS activities and bring some suggestions for such deficiencies to be mitigated or eradicated.